Fibroblasts, an inconspicuous but essential player in colon cancer development and progression - Mukaida, Naofumi (World J Gastroenterol, 2016)
Tumor microenvironments have a crucial role in cancer initiation and progression, and share many molecular and pathological features with wound healing process. Unless treated, tumors, however, do not heal in contrast to wounds that heal within a limited time framework. Wounds heal in coordination of a myriad of types of cells, particularly endothelial cells, leukocytes, and fibroblasts. Similar sets of cells also contribute to cancer initiation and progression, and as a consequence, anti-cancer treatment strategies have been proposed and tested by targeting endothelial cells and/or leukocytes. Compared with endothelial cells and leukocytes, less attention has been paid to the roles of cancer-associated fibroblasts (CAFs), fibroblasts present in tumor tissues, because their heterogeneity hinders the elucidation on them at cellular and molecular levels. Here, we will discuss the origin of CAFs and their crucial roles in cancer initiation and progression, and the possibility to develop a novel type of anti-cancer treatment by manipulating the migration and functions of CAFs.